Usage of public financial support services, entrepreneurial orientation and SME performance: the case of Malaysia - Mohd Nor Hakimin Bin Yusoff; Fakhrul Anwar Zainol; Mohamad Ismail; Jati Kasuma; Dio Caisar Darma (Financial Internet Quarterly, 2021)
SMEs have received much recognition as they continue to be the backbone in the development and economic growth of nations. This study intended to investigate how the entrepreneurial orientation moderates the relationship between the utilization of the financial support services and the firm's performance. This study used Structural Equation Modeling to evaluate the impact of financial support services on SME performance. The sample for this study involved SMEs in Malaysia. The result indicates that financial support services significantly associated with the firms' performance and entrepreneurial orientation failed to influence significantly the relationship between the usage of the services and the performance. The findings of this study could be useful for the government business support services providers to enhance further the quality of services and will provide an understanding of how effectively the characteristics of SMEs related to entrepreneurial orientation would help increase the effectiveness of the support services.
Keywords: L26; G1; L1; M29; 330; entrepreneurial orientation; financial support services; performance; SMEs; SEM-PLS